1998
DOI: 10.1038/29808
|View full text |Cite|
|
Sign up to set email alerts
|

FGF-mediated mesoderm induction involves the Src-family kinase Laloo

Abstract: During embryogenesis, inductive interactions underlie the development of much of the body plan. In Xenopus laevis, factors secreted from the vegetal pole induce mesoderm in the adjacent marginal zone; members of both the transforming growth factor-beta (TGF-beta) and fibroblast growth factor (FGF) ligand families seem to have critical roles in this process. Here we report the identification and characterization of laloo, a novel participant in the signal transduction cascade linking extracellular, mesoderm-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 28 publications
2
65
1
Order By: Relevance
“…Although FGF is not thought to function as a primary mesoderm inducer in vivo, exogenous FGF can induce mesoderm in ectodermal explants (27). The Xctr1-interacting protein, Laloo, is required for FGF-mediated mesoderm induction and induces expression of the early panmesodermal gene Xbrachyury (Xbra) in gastrula-stage animal cap explants (9). Xctr1 RNA injection alone does not induce Xbra expression in this assay ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although FGF is not thought to function as a primary mesoderm inducer in vivo, exogenous FGF can induce mesoderm in ectodermal explants (27). The Xctr1-interacting protein, Laloo, is required for FGF-mediated mesoderm induction and induces expression of the early panmesodermal gene Xbrachyury (Xbra) in gastrula-stage animal cap explants (9). Xctr1 RNA injection alone does not induce Xbra expression in this assay ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A dramatic example of this phenomenon occurs during early vertebrate embryogenesis, when fibroblast growth factor (FGF) mediates multiple developmental processes. During mesoderm induction, FGF triggers activation of a Ras-MAPK cascade (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In contrast, subsequent morphogenesis of the dorsal mesoderm is regulated by a noncanonical FGF pathway that is independent of Ras-MAPK signaling and may involve stimulation of Ca 2ϩ release and/or activation of phospholipase C␥ (PLC␥) (13,14).…”
Section: Xenopus ͉ Fgf ͉ Pluripotent ͉ Erk ͉ Laloomentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on Xenopus laevis have demonstrated that Laloo, a novel member of the Src family of tyrosine kinases, is required for mesoderm induction in response to FGF (13). The cooperation of FRS2 and Laloo in this pathway is suggested by the observed association of FRS2 with Laloo (14,15).…”
mentioning
confidence: 92%
“…An activated FGF receptor 1, like several FGF signaling pathway elements (Pownall et al, 1996;Tada et al, 1997;Weinstein et al, 1998;Brewster et al, 2000;Hama et al, 2001;Park et al, 2004), induces ectopic structures. Several members of the Met signaling pathway are also common to the FGF signaling pathway (Furge et al, 2000; Powers et al, 2000), including Ras/Raf/Mek/MAPK.…”
Section: Tpr-met Induces Ectopic Structures a Ishimura Et Almentioning
confidence: 99%